Benefits of freeze dried arabica coffee peels (Coffea arabica) as an oral antimicrobial : Manfaat kulit buah kopi arabika kering beku (Coffea arabica) sebagai antimikroba oral - Agus Sumono; Tecky Indriana; Yuni Mulya Utami; Disaera (Makassar Dental Journal, 2022)
Background: Oral infections are currently treated with synthetic drugs, namely antimicrobials (antibiotics and antifungals) that can cause resistant bacteria, so alternative antimicrobials from herbal groups are needed. Arabica coffee peel contains phytoche-mical compounds (polyphenols, alkaloids, saponins) which have potential as natural antibacterial. Purpose:To examine the benefits of waste of arabica coffee rind in inhibiting growth of Streptococcus mutans, Porphyromonas gingivalis and Candida albicans. Methods: This experimental laboratory with the post test only group design was started with making of freeze dried coffee peels 25%, 50% and 75%; positive control used chlorhexidine and nystatin. The antimicrobial test method was performed by the diffusion method and the growth of microbial colonies was calculated using a colony counter. Result: Antimicrobial effect increased at all concentration of test solutions to the three microbes. This shows that there is a strong positive relationship between concentration and the number of microbial colonies. The higher concentration of dried arabica coffee peels, the greater the effect of microbial killing power. The biggest effect is on C.albicans, P.gingivalis, S.mutans, consecutively. Conclusion: arabica coffee fruit skin can be used as an antimicrobial oral cavity against the growth of S.mutans, P.gingivalis and C.albicans.